ALQUR’AN DAN ETIKA BERBISNIS - Nursyamsu Nursyamsu (Fakultas Syariah Institut Agama Islam Negeri Palu, 2017)
One of the activities in carrying out economic activity is doingbusiness, in the business needed values, so as not to be separated fromthe corridors that can lead to a business activity does not providebenefits, even bring harm. Business values in economic activities arenecessary as the main rule in running a business activity. As a hint, theQur'an is a major source in which various rules govern how to carryout business activities. Ethics is seen as a must-have on any businessactivity that can be seen in the behavior of a businessperson. Thispaper discusses the ethics of business in the perspective of the Qur'an.